How to Search and Cite References from Google Scholar - Al Husaeni, Dwi Novia; Al Husaeni, Dwi Fitria; Nandiyanto, Asep Bayu Dani (ASEAN Journal of Educational Research and Technology, 2023)
Each scientific paper contains references that can be used as a means of accountability for the author. Therefore, references are things that must be considered in writing scientific papers. The purpose of this study is to provide an example and demonstrate an easy way to cite and search for references from Google Scholar. The research method used is an experiment method with a literature study. An internet connection is required to open the Google Scholar search engine. The steps of this research consist of looking for articles in journals, getting citations, and building reference styles. There are several reference styles used in writing scientific papers, such as APA, MLA, Vancouver, Harvard, Chicago/Turabian, and IEEE styles. We identified that Google Scholar can be used as a tool that can assist in finding writing sources. Even though it requires an internet connection, Google Scholar makes it easy for writers to choose the reference style to use by using the "cite" button.